Using Landscape analysis techniques to prevent silt accumulation in the reservoir of the Dwerige weir project and developing River basin, Missan, South Eastern IRAQ - Al- Siaede, Riaed (Iraqi Journal of Science, 2022)
Water harvesting techniques developed globally during the last decades with highly increasing water crisis and climate changes. The Yeoman keyline method was spread widely with increased use for sustainable permaculture development. The main aim of the current study is to analyze and solve the siltation problem in Dwerige weir and to develop water resources in the basin area. The remote sensing data, field surveying, and hydrology are used together to build a new geotechnical approach. The results show that a huge siltation quantity was not considered in the weir design studies, which were represented by sand sheet materials and eroded soils washed by flooding and entering the weir reservoir through four main channels. The topography and hydrology of the study area are analysed, and the key points- keylines principle used by selecting the suitable contour lines to dig trenches along them to control soil erosion by decreasing flow velocity and holding part of floodwater to increase soil water content and recharge groundwater. The floodwater quantities are estimated in normal and storm cases, finally, the extra drain water is evaluated.